2014
DOI: 10.29244/fagb.4.2.153-170
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Saing Dan Dampak Kebijakan Pemerintah Terhadap Komoditas Teh (Studi Kasus: PTPN Viii Afdeling Rancabali Iii)

Abstract: Rancabali III department, National Plantation VIII produces tea with national and international standard of quality. The purpose of this study are to analyze the effect of  government policies, increase of output price, increase of  chemical fertilizer price, and  production number decline to orthodox black tea competitiveness at Rancabali III department, National Plantation VIII. The methods are Policy Analysis Matrix and sensitivity analysis. The result shows that government policies, output price, chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Hal tersebut mencerminkan bahwa Komoditas kakao dapat berdaya saing secara kompetitif dan komparatif. Keunggulan kompetititfnya dapat dilihat dari nilai keuntungan rasio biaya, sedangkan keunggulan komparatif dapat dilihat dari hasil keuntungan rasio sumberdaya domestik Aliyatillah dan Kusnadi (2011).…”
Section: Gambar 1 Nilai Ide Sektor Pertanian (Diolah 2022)unclassified
“…Hal tersebut mencerminkan bahwa Komoditas kakao dapat berdaya saing secara kompetitif dan komparatif. Keunggulan kompetititfnya dapat dilihat dari nilai keuntungan rasio biaya, sedangkan keunggulan komparatif dapat dilihat dari hasil keuntungan rasio sumberdaya domestik Aliyatillah dan Kusnadi (2011).…”
Section: Gambar 1 Nilai Ide Sektor Pertanian (Diolah 2022)unclassified
“…Based on these circumstances, it may be concluded that tradable inputs in the domestic market are more profitable for sorghum farmers because the input price is lower than if farmers use tradable inputs in the international market or by using social prices. The divergence in tradable inputs in sorghum farming occurs due to government policy on import duty taxes on production inputs such as fertilizers and medicines at 5% and VAT at 10% (Rahmi et al, 2013).…”
Section: Policy Analysis Matrixmentioning
confidence: 99%
“…Tahun 2010, produktivitas teh Indonesia 1,2 ton/ha, sementara Malaysia mencapai produktivitas hingga 8 ton/ha. Meskipun Indonesia memiliki sumberdaya yang besar, rendahnya produktivitas ini menyebabkan daya saing industri teh lemah (Rahmi, 2014).…”
Section: Pendahuluanunclassified